2003
DOI: 10.1007/bf02436280
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the longitudinal structure of the early hominid foot: A two-dimensional architecture analysis

Abstract: Early hominid feet are often very fragmentary preserved and their architectural approaches stayed limited and subject to controversy. This study proposes an architectural analysis of the primate foot realised on dislocated skeleton. It is based on the angular analysis of geometrical relationships between the joint areas. We investigate the longitudinal structure of the primate foot and we present the results conceming some Australopithecus afarensis specimens from Hadar (Ethiopia) and the Homo habilis Olduvai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 20 publications
2
34
2
Order By: Relevance
“…Nevertheless, various papers have argued that anatomical features in A. afarensis skeletal elements, including a large navicular tuberosity [5] and a well-marked peroneal groove on the fibular malleolus [55] are evidence that the medial midfoot of A. afarensis was weight-bearing, and thus that the species lacked transverse arches and/or a medial longitudinal arch. A two-dimensional analysis of articular orientations [56] also came to the same conclusion. However, a recent paper [51] argues that the form of a new fourth metatarsal of A. afarensis indicates, contrariwise, that this species did indeed have a medial longitudinal arch and lacked a mid-tarsal break.…”
Section: 44supporting
confidence: 55%
“…Nevertheless, various papers have argued that anatomical features in A. afarensis skeletal elements, including a large navicular tuberosity [5] and a well-marked peroneal groove on the fibular malleolus [55] are evidence that the medial midfoot of A. afarensis was weight-bearing, and thus that the species lacked transverse arches and/or a medial longitudinal arch. A two-dimensional analysis of articular orientations [56] also came to the same conclusion. However, a recent paper [51] argues that the form of a new fourth metatarsal of A. afarensis indicates, contrariwise, that this species did indeed have a medial longitudinal arch and lacked a mid-tarsal break.…”
Section: 44supporting
confidence: 55%
“…If the latter is correct, then some South African australopiths, while possessing a rigid lateral foot and lateral longitudinal arch (DeSilva, 2010), would have a lower and less developed medial longitudinal arch. This reconstruction of the foot would be consistent with seemingly contradictory studies finding evidence for an arch in australopiths using bones found in the lateral column (e.g., DeSilva, 2010;Ward et al, 2011), but the absence of an arch in the medial column (e.g., Berillon, 2003;Harcourt-Smith and Aiello, 2004). However, we caution about over-generalizing the arch given the range of variation in arch development in humans today and evidence that such variation may have existed in australopiths as well (DeSilva and Throckmorton, 2010).…”
Section: Explaining the Internal Torsion Of The Metatarsal Headsupporting
confidence: 58%
“…It does not include three out of five great ape species, and fails to test for alternate behaviors which may be associated to or result in these putatively bipedal characters. Moreover, the study also fails to demonstrate a causal relationship between the cited characters and the functions ascribed to them, and ignores much of the literature which quantifies African ape-like characters in the Hadar foot (Berillon, 2003(Berillon, , 2004Deloison, 2004;Sarmiento and Marcus, 2000;Stern and Susman, 1983;Susman et al, 1984). Considering that evolution proceeds as behavioral shifts through structural continuity, and necessitates localized anatomical structure to have at least a duality of function (Darwin, 1859), Ward et al's (2011a,b) claims of bipedal exclusivity for so many 4th MT characters require testing.…”
Section: Introductionmentioning
confidence: 83%
“…4a, refers the reader to reference 11, Berillon (2003), as the source of the measurements and method for measuring 4th MT cuboid facet curvature. Berillon (2003), however, does not report on 4th MT cuboid facet curvature. We suspect that Ward et al intended to reference DeSilva (2010), which in their study appears as reference 10, DeSilva (2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation